Question

what is (x+h)^3

258

likes1292 views

Rasheed

4.7

33 Answers

To expand the expression (x + h)^3 , we can use the binomial theorem. The binomial theorem states that for any real numbers a and b and any positive integer n , the expansion of (a + b)^n can be written as:

(a + b)^n = \binom{n}{0}a^n b^0 + \binom{n}{1}a^{n-1} b^1 + \binom{n}{2}a^{n-2} b^2 + \ldots + \binom{n}{n-1}a^1 b^{n-1} + \binom{n}{n}a^0 b^n

where\binom{n}{k} represents the binomial coefficient, and is equal to \frac{n!}{k!(n-k)!} .

In our case,a = x and b = h , so we can substitute these values into the binomial theorem formula:

(x + h)^3 = \binom{3}{0}x^3h^0 + \binom{3}{1}x^2h^1 + \binom{3}{2}x^1h^2 + \binom{3}{3}x^0h^3

Simplifying each term:

\binom{3}{0}x^3h^0 = 1x^3h^0 = x^3

\binom{3}{1}x^2h^1 = 3x^2h^1 = 3x^2h

\binom{3}{2}x^1h^2 = 3x^1h^2 = 3xh^2

\binom{3}{3}x^0h^3 = 1x^0h^3 = h^3

Now we can combine all the terms:

(x + h)^3 = x^3 + 3x^2h + 3xh^2 + h^3

Therefore, the expansion of(x + h)^3 is x^3 + 3x^2h + 3xh^2 + h^3 .

Answer:(x + h)^3 = x^3 + 3x^2h + 3xh^2 + h^3

where

In our case,

Simplifying each term:

Now we can combine all the terms:

Therefore, the expansion of

Answer:

Frequently asked questions (FAQs)

What is the simplified derivative of e^(3x) * sin(2x) with respect to x?

+

Math question: What is the maximum value of the function f(x) = x^3 - 4x^2 + 5x - 2 on the interval [-2, 3]?

+

What is the probability of getting exactly 4 heads in 6 flips of a fair coin?

+

New questions in Mathematics